Petrology of the Southeastern Part of the Gunung Jerai - B Md Ghazali, Luqman Hakim (Universiti Teknologi PETRONAS, 2016)
This project is to study about the petrology of the southeastern part of the Gunung Jerai. The objective of this study is to understand the distribution of the rocks by constructing the geological map and understand the degree of the metamorphism occur in the southeastern part of Gunung Jerai. The southeastern part of Gunung Jerai is dominated by metamorphic rocks followed by igneous rocks. The metamorphic rocks present are quartzite and hornfels while the igneous rocks found are granite and pegmatite. The metamorphic rocks formed in the area by contact metamorphism mechanism and produce low grade metamorphic rocks with no foliation. The analysis done on the samples of the rocks shows the exact characteristics and properties of the rocks. The findings of this study can be correlated with the previous study done by other researchers, with the addition of hornfels in the proposed geological map.